Ethical Dilemma in the Age of Automation: A Case Study of Leadership, Loyalty, and Organizational Change - Jamak Amrollahifar; Guo Yajie; Maruf, Tarekol Islam (IIUM Journal of Case Studies in Management, 2025)
This case study explores the ethical and emotional challenges faced by a senior technical engineering leader, Mr. Jason, in a manufacturing company in Miami, USA. With over two decades of service, Jason is tasked by top management to propose cost-saving solutions amid financial pressure and the advent of automation. His solution involves reducing manual labour through automation—yet it creates a moral dilemma, as his recommendation could lead to job loss for his close friend and long-time co-worker. This case highlights the human side of technological transitions and invites discussion around ethics, leadership responsibility, and strategic decision-making.